2021
DOI: 10.1111/ijfs.15532
|View full text |Cite
|
Sign up to set email alerts
|

Presence of perfluoroalkyl substances in Mediterranean sea and North Italian lake fish addressed to Italian consumer

Abstract: Summary The primary source of perfluoroalkyl substances (PFASs) exposure is the diet, mainly fish. Seabass (Dicentrarchus labrax) and seabream (Sparus aurata) are among the most consumed sea fish in Italy. Fish from Northern Italy lakes like perch (Perca fluviatilis) is of particular importance in terms of consumption volume, while Mediterranean shad (Alosa agone) and European whitefish (Coregonus lavaretus) represent niche consumption. These species too could be a cause of consumer exposure to PFAS. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…As regards fish consumption in Italy, in a recent work [ 22 ], we faced a substantial lack of data about the consumption of niche lake food such as agone, a very typical fish found in north Italian lakes. Briefly, we started from a EUMOFA ‘Case study about the price structure in the supply chain for fresh gilthead seabream in Italy’ [ 19 ] to calculate the daily consumption of the lake fish as well as for sea fish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards fish consumption in Italy, in a recent work [ 22 ], we faced a substantial lack of data about the consumption of niche lake food such as agone, a very typical fish found in north Italian lakes. Briefly, we started from a EUMOFA ‘Case study about the price structure in the supply chain for fresh gilthead seabream in Italy’ [ 19 ] to calculate the daily consumption of the lake fish as well as for sea fish.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, there are few recent studies on the detection of POPs in sea fish or in lake fish ( Table 1 ), and none have dealt with both sea fish and lake fish in order to more comprehensively analyze the risks faced by different consumers, as we had in a recent article dealing with PFASs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…River waters were collected as grab samples because, given the surfactant properties of these compounds, US EPA (Environmental Protection Agency) does not recommend composite sampling (US EPA 2022). The choice of the most appropriate monitoring sites was made on the basis of a previous study conducted by the ARPA Umbria regional agency for environmental protection, as reported by Nucci et al (2019a, b) and by Charavgis et al (2022). The results obtained from this previous investigation highlighted the necessity of monthly monitoring of PFCs, both in rivers where the concentrations of these substances exceeded the maximum levels fixed by directive 2013/39/EU (European Commission 2013) and in those rivers affected by significant sources of urban, agricultural and industrial pollution, which are NES, CAI, GEN, TVN rivers identified in Table 1.…”
Section: Sample Collectionmentioning
confidence: 99%
“…In particular, scientific evidence demonstrated that PFCs can inhibit algae growth, induce cytotoxic and genotoxic effects on invertebrates and fishes and cause serious negative outcomes on amphibians (Latała et al 2009;Liu et al 2014;Kim et al 2015;Ayanda et al 2018;Savoca and Pace 2021). In Italy, the analytical determination of these substances in water samples started in 2013, after the discovery of a massive groundwater contamination in a vast area in northern Italy (Valsecchi et al 2015;Bonelli et al 2020;Chiesa et al 2022). Although the nature of these pollutants does not exclude large-scale distribution, the determination of PFAs was carried out only in the surface waters of northern Italy.…”
mentioning
confidence: 99%
“…Giari et al compared European eels caught in the Po River and in the Comacchio Lagoon and, in a further study, expanded the investigation to other fish species from the Po River, including bleak, channel catfish, and barbel [ 24 , 25 ]. Chiesa et al monitored 16 PFASs in Garda Lake European eel and European perch, which are among the most consumed freshwater species [ 26 , 27 ]. PFASs were also studied in aquatic species from Varese Lake, Mergozzo Lake, and other subalpine Italian lakes [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%